PERANCANGAN AMBIENT MEDIA SEBAGAI SARANA PROMOSI PERMAINAN TRADISIONAL KOMUNITAS ANAK BAWANG SURAKARTA - Vikhi Fikraturrosyida; Taufik Murtono (TEXTURE : Art and Culture Journal, 2018)
Ambient Media Designing as a means of Promoting Traditional Games The Children Community of Onion Surakarta has the idea of introducing traditional games to today's modern children who are starting to forget them. This process uses a combination of Garvin Ambrose and Paul Harris methods, and Bambang Sukma Wijaya's ambient media design strategy. This design model explains the stages that are passed in the process of designing ambient media and supporting promotional media. The stage includes identification of data, research methods, formulation of ideas, brainstorming, sketching, digital, and making prototypes. The search for ambient media ideas is done by using the concept of triangle insight which combines knowledge about consumers, products and mediums / places. After that, the results of the triangle insight were obtained where the children who went to Taman Cerdas spent more time playing online games because there was free access Wi-Fi available. Through these insights, the idea of designing ambient media was obtained at Taman Cerdas Jebres Surakarta by introducing hide and seek games, while also designing ambient media at Mojosongo's garden food court to introduce doom-playing games. As for the design of supporting promotional media to produce several items such as shirts, pillows, pins, note books, bookmarks to paper bags. This design is expected to become a new breakthrough in introducing traditional games to children aged 7-13 years and is expected to make old people aware of the benefits of traditional social, psychological, and physical games. The design is made in a unique way or can be called ambient media aimed at strengthening the message that you want to convey and giving a shock effect to the target so that it gives an unforgettable impression.Keywords: Traditional games, ambient media, promotion design